Upaya Bimbingan Konseling Meningkatkan Disiplin Positif Siswa Dalam Tinjauan Ontologi Epistemologi Dan Aksiologi Filsafat Ilmu - Lestari, Wiwi Widya; Silalahi, Suandi (Universitas Sultan Ageng Tirtayasa, 2024)
Implementation of counseling guidance services increases students' positive discipline from the perspective of the philosophy of science through descriptions of the meaning, function and philosophical principles of counseling guidance, ontology in counseling guidance, epistemology in counseling guidance and axiology in counseling guidance. This research uses a qualitative approach with literature analysis as the main method. Data sources from various libraries such as books and scientific articles. Data analysis using qualitative descriptive. The research results show that the scientific basis for counseling guidance in an effort to improve students' positive discipline is in synergy with an ontological understanding of humans as complex and dynamic creatures, an interdisciplinary epistemological approach and an axiological commitment to individual welfare.